2015
DOI: 10.1007/s12291-015-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oestrogen on Altering the Serum and Urinary Levels of Calcium, Phosphate and Magnesium in Hysterectomised Women Compared to Natural Menopausal South Indian Women: A Case Control Study

Abstract: Given the paucity of studies conducted to know the effect of suddenness and earlier onset of endocrinological changes associated with hysterectomy, on the serum and urinary levels of calcium, magnesium and phosphate the present study was conducted to compare the levels of calcium, magnesium and phosphate in serum and urine of hysterectomised and natural menopausal south Indian women. This is a cross-sectional observational study. The study included three groups of 30 healthy premenopausal, 30 early surgical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Conversely, the re-absorption and excretion of magnesium in kidneys are influenced by several unclarified mechanisms, such as different hormone regulation [20]. It was reported that either lower or higher serum magnesium was observed among natural postmenopausal women, nevertheless, estrogen therapy could decrease its secretion in urine [2123]. By contrast, we found that the secretion of magnesium in 24-hour urine was statistically lower among postmenopausal women than among non-menopausal women.…”
Section: Discussioncontrasting
confidence: 55%
“…Conversely, the re-absorption and excretion of magnesium in kidneys are influenced by several unclarified mechanisms, such as different hormone regulation [20]. It was reported that either lower or higher serum magnesium was observed among natural postmenopausal women, nevertheless, estrogen therapy could decrease its secretion in urine [2123]. By contrast, we found that the secretion of magnesium in 24-hour urine was statistically lower among postmenopausal women than among non-menopausal women.…”
Section: Discussioncontrasting
confidence: 55%
“…It was shown in one of the study that serum calcium decreased, but in contrast to the present study ,serum magnesium increased in postmenopausal women when compared to premenopausal women. 21 Also there was increased urinary calcium/ creatinine and urine magnesium/creatinine ratio. Decrease in oestrogen causes decreased activity of osteoblasts and increased activity of osteoclasts causing demineralization and ultimately osteoporosis in postmenopausal women.…”
Section: Discussionmentioning
confidence: 96%
“…Elevated levels of muscle Mg 2+ in the EF phase may effectively counteract Ca 2+ to mitigate muscle spasms or twitches resulting from excessive muscle contraction due to Ca 2+ accumulation. Furthermore, it is noteworthy that natural postmenopausal women typically exhibit lower serum estrogen levels in conjunction with higher magnesium levels when compared to healthy premenopausal women [54]. Additionally, estrogen supplementation has been shown to reduce the hypermagnesuria observed in postmenopausal women [55].…”
Section: Ph and Free Mg Measurementsmentioning
confidence: 99%